The political scene, the scene policy: Reflections on modernity in German theatrical architecture (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The present work had as a starting point the propositions about scenic space brought by the book The revolution in the theater: conclusions concerning the Theater of the Artists of Munich of the German dramatist and director Georg Fuchs. The article revisited the theatrical architectures developed by German artists of the early 20th century and from them, reflected on the political proposals contained in the works of directors Max Reinhardt and Erwin Piscator. The objective here was to reflect on the relationships between scenic and political space, and how they were decisive in the construction of modern theater.
Keywords: Scenic space; Political theater; German theater; Modernity; Theatrical architecture